Transcranial Random Noise Stimulation Does Not Improve Behavioral and Neurophysiological Measures in Patients with Subacute Vegetative-Unresponsive Wakefulness State (VS-UWS) - Mancuso, Mauro; Abbruzzese, Laura; Canova, Stefania; Landi, Giulia; Rossi, Simone; Santarnecchi, Emiliano (Frontiers in Human Neuroscience, 2017)
Background: The absence of efficient treatments capable to promote central nervous system recovery in Vegetative State (VS) patients due to a severe acquired brain injury highlights the need of exploring alternative neuromodulatory treatments that can lead to neurobehavioural gains. Some encouraging preliminary observations suggest that transcranial Direct Current Stimulation (tDCS) could be effective in Disorders of Consciousness (DoC) patients, especially when applied on the dorsolateral prefrontal cortex (DLPFC) in patients with minimally conscious state(MCS) but not in those with vegetative state (VS). Objective: The primary aim of the present study was to verify if the application of transcranial random noise stimulation (tRNS) on the DLPFC might favour improvements of consciousness recovery in subacute VS-UWS. Methods: Nine patients with DoC due to traumatic brain injury (TBI) (n=1), anoxia (n=3), and vascular damage (n=5) have undergone a randomized, double-blind, sham-controlled, neuromodulatory trial with tRNS of the DLPFC. All patient were in a post-acute phase and onset ranged from 30 days to 4 months. The diagnosis of DoC was based on internationally established criteria from the Multi-Society Task Force on PVS, (1994) and classified as VS or MCS using the JFK Coma Recovery Scale-Revised scores (CRS-R). We used CRS-R, Synek Scale, Ad-Hoc Semi-quantitative Scale and the Clinical Global Impression-Improvement (CGI-I) scale to measure behavioural and electrophysiological changes. All patients were also treated with daily conventional rehabilitation treatment. Results: No significant differences emerged between active and sham groups regarding consciousness improvement, as well as electroencephalographic findings. Thus, despite the early neuromodulatory intervention performed in the subacute phase, we did not observe significant effects of the tRNS stimulation, neither behaviourally nor on brain activity. Only one patient showed emergence from VS-UWS, evolving from VS to minimally conscious state (MCS) after the tRNS stimulation, at a distance of three weeks from the enrolment into the study. Conclusions: repeated applications of tRNS of the DLPFC, even if applied in a subacute phase of VS-UWS state, did not modify behavioural and neurophysiological outcomes more than sham stimulation.